Left Brain/Right Brain Mythology and Implications for Management and Training - Hines, Terence (Academy of Management Review, 1987)
The claim has been made that functional differences between the two hemispheres of the human brain have practical implications for management and training practices. This paper reviews research on hemispheric differences and finds that such claims represent a “hemisphere mythology” that is contradicted by research on the nature of the differences between the hemispheres.